Left Transperitoneal Adrenalectomy with a Laparoendoscopic Single-Site Surgery Combined Technique: Initial Case Reports - Yasuhiro Sumino; Daisaku Nakano; Ken-Ichi Mori; Takeo Nomura; Fuminori Sato; Hiromitsu Mimata (Case Reports in Medicine)
Laparoendoscopic single-site surgery (LESS) is a step toward the development of minimally invasive surgery. It is initially difficult for surgeons with limited experience to perform the surgery. We describe two cases of left adrenalectomy with a LESS combined with the addition of an accessory port. After a 2.5-cm skin incision was made at the level of the paraumbilicus to insert the primary 12-mm trocar for the laparoscope, a 5-mm nonbladed trocar was placed through the skin incision side-by-side with the primary trocar. A second 3-mm nonbladed trocar was then placed along the anterior axillary line; a multichannel trocar was not used as a single port. Both adrenalectomies were completed successfully. In patients with a minor adrenal tumor, a combined technique using LESS and an additional port is easier than LESS alone and may, therefore, be a bridge between the conventional laparoscopic approach and LESS.